2020
DOI: 10.3390/cancers12092522
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Small Cell Lung Cancer

Abstract: Small-cell lung cancer (SCLC) is an aggressive tumor type with limited therapeutic options and poor prognosis. Chemotherapy regimens containing platinum represent the cornerstone of treatment for patients with extensive disease, but there has been no real progress for 30 years. The evidence that SCLC is characterized by a high mutational burden led to the development of immune-checkpoint inhibitors as single agents or in combination with chemotherapy. Randomized phase III trials demonstrated that the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 48 publications
1
67
0
1
Order By: Relevance
“…On the other hand, first-line treatment in patients with ED-SCLC is undergoing great changes, especially in the field of immunotherapy. For example, blocking the programmed death 1 receptor (PD-1) or its ligand (PD-L1) pathway has been shown to improve the prognosis of patients with ED-SCLC [ 18 , 19 ]. The Impower 133 (NCT02763579) and CASPIAN phase III trials (NCT03043872) demonstrated that adding atezolizumab or durvalumab to platinum plus etoposide chemotherapy improves OS and progression-free survival (PFS) compared to chemotherapy alone [ 20 , 21 ].…”
Section: Clinical Management Of Sclcmentioning
confidence: 99%
“…On the other hand, first-line treatment in patients with ED-SCLC is undergoing great changes, especially in the field of immunotherapy. For example, blocking the programmed death 1 receptor (PD-1) or its ligand (PD-L1) pathway has been shown to improve the prognosis of patients with ED-SCLC [ 18 , 19 ]. The Impower 133 (NCT02763579) and CASPIAN phase III trials (NCT03043872) demonstrated that adding atezolizumab or durvalumab to platinum plus etoposide chemotherapy improves OS and progression-free survival (PFS) compared to chemotherapy alone [ 20 , 21 ].…”
Section: Clinical Management Of Sclcmentioning
confidence: 99%
“…The prognosis of patients with LS-SCLC is better than those with ES-SCLC, the survival time of patients with LS-SCLC ranges from 15 to 20 months and their 5-year survival rate is ~20–25%. In comparison, the survival time of patients with ES-SCLC ranges from 8 to 13 months, with a 5-year survival rate of only about 2% ( 3 , 4 ). Unfortunately, ~70% of SCLC patients are diagnosed with ES-SCLC ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…An improved overall survival rate was seen in patients with high PD-L1 expression (16,17). Not all lung cancer indications require a PD-L1 protein measurement, including the first-line treatment of patients with squamous or non-squamous NSCLC as a single agent or in combination with carboplatin and either paclitaxel or nabpaclitaxel (18,19) or patients with SCLC with disease progression on or after platinum-based chemotherapy, and at least one other prior line of therapy (20,21). In these clinical studies, patients demonstrated benefit regardless of the level of PD-L1 expression.…”
Section: Pembrolizumab (Keytruda)mentioning
confidence: 99%